A Google Trends analysis of people's sense of seasons in Hokkaido - Shin, Nagai; Nakagawa, Hiromi; Morimoto, Hiroshi; Kotani, Ayumi (Frontiers in Sustainable Tourism, 2024)
Accurate evaluation of the spatiotemporal variability of people's interest in seasons (i.e., their “sense of seasons”) is required to deeply understand temporal changes in the relationship between people and landscape under climate and societal changes. To this end, it is useful to analyze the time series of relative search volume (RSV) for relevant search terms extracted from Google Trends (GT) for any target period and target area. We examined the presence and absence of 12-month seasonality of the time series of RSV for about 300 representative search terms for Hokkaido in Japan, which has vast natural resources and is visited year-round by many tourists from Japan and abroad. In the case of searchers in both all of Japan and Hokkaido alone, search terms categorized into the foods, leisure, natural scenic spots, and seafood fields showed a strong trend toward 12-month seasonality of the time series of RSV, whereas those categorized into the Ainu (indigenous people) and people fields had weak trends for 12-month seasonality. People's sense of seasons in all of Japan or Hokkaido alone was likely associated with tourism (search terms in the animals, festivals, foods, leisure, natural scenic spots, seafood, tourist spots, and vegetation fields), as well as with animal and plant phenology (terms in the animals and vegetation fields), provisioning ecosystem services (terms in the foods and seafood fields), climate (terms in the climate field), and cultural ecosystem services (terms in the animals, festival, foods, leisure, natural scenic spots, seafoods, and vegetation fields). However, search terms with no 12-month seasonality were included in the tourist spots fields: they included many tourist spots visited by tourists all year around. Despite the need to appropriately select a huge number of representative search terms to reduce the effect of GT limitations and the uncertainty caused by unexpected and rapid temporal changes in RSV, the GT analysis allowed us to evaluate the spatiotemporal variability of people's sense of seasons regarding various objects in the landscape, including those related to tourism, under climate and societal changes.